AN ANALYSIS ILLOCUTIONARY ACT IN THE MONSTER HOUSE MOVIE - Abraham Ignatius Heriyanto; Susie Chrismalia Garnida (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
The purpose of this research is to analyze the types of illocutionary act in the Monster House movie. This study uses the speech act theory that focus on the illocutionary act by Searle theory (1979) – assertive, directive, declarative, expressive, and commissive. This study uses qualitative research by watching the movie, reading the script as a support of the movie, classifying the data, and analyzing the data to find the types and the meaning of illocutionary act, and the types of illocutionary act most frequently used in the Monster House movie that focuses to the linguistic theories derived from related literature sources. The writer finds 133 utterances of illocutionary acts used by characters of the Monster House movie. They consist of 37 assertive utterances, 59 directive utterances, 3 declarative utterances, 32 expressive utterances, and 2 commissive utterances. The dominant type is directive that DJ commands his friends in many scenes where he seems to manage the situations when they are inspecting the haunted called Monster House that he accidentally is a leader among his friends